Experimental investigation of liquid-vapor ejector with conical mixing chamber - Sharapov, Sergii; Arsenyev, Vyacheslav; Kozin, Viktor (Technology audit and production reserves, 2016)
The article is devoted the design of working process of liquid-vapor ejector of a vacuum unit with conical mixing chamber, working on principle of stream thermocompression, research of influence of thermodynamic parameters and descriptions of active and passive streams on the process of mixing with the purpose of achievement of most vacuum unit efficiency. The main content of the article is study the nature of passive mixing flows with different thermodynamic properties on the geometric parameters of the mixing chamber. Experimental study of liquid-vapor ejector with conical mixing chamber on a transparent model allowed to confirm the mechanism of the working process at pressures below atmospheric pressure, namely the boiling of metastable superheated liquid, characterized by the presence of three critical sections expiry of expanding the channels to the definition section of flow separation from the walls of the channel and its position relative to the nozzle exit of active flow. Also the nature of the mixing process in the chambers of conical shape is investigated. It allows establishing maximum efficiency by optimizing the flow of liquid-vapor ejector with conical mixing chamber. The estimation of the appropriateness of units on the basis of LVE in vacuum systems through a comparative exergy analysis of basic and alternative schemes offered by the method of J. Tsatsaronis.